BETA-BLOCKERS IN SPORT: PHYSIOLOGICAL EFFECTS, PERFORMANCE IMPLICATIONS AND REGULATORY PERSPECTIVES - Szymon Rudawski; Magdalena Zięba; Magdalena Morytko; Maja Elertowicz; Mikołaj Moskwa; Patrycja Herod; Aleksandra Wójciak; Kateryna Shtohryn; Hubert Gugulski (International Journal of Innovative Technologies in Social Science, 2025)
Introduction: Beta-blockers are a pharmacological class widely used in cardiovascular and anxiety-related conditions. Their ability to reduce heart rate, reduce physiological tremor and attenuate sympathetic arousal has led to increasing interest regarding their use in sport. While beta-blockers impair endurance performance, they may enhance precision and emotional stability in sports requiring fine motor control. This has resulted in selective regulation by anti-doping authorities. Aim of the study: The aim of this article was to review the current evidence on physiological effects of beta-blockers in athletes and to evaluate their sport-specific implications, including their relevance to anti-doping regulations. Methods and Materials: Literature was reviewed using PubMed, Scopus and Google Scholar databases, focusing primarily on experimental human studies, controlled trials and mechanistic analyses investigating beta-blocker pharmacology and athletic performance. Key search terms included: “beta-blockers”, “sport performance”, “precision sports”, “beta receptors”, and “doping”. Conclusion: Evidence indicates that beta-blockers exert mixed performance effects depending on sport characteristics. They consistently reduce endurance capacity by limiting cardiac output and metabolic efficiency, yet can benefit athletes in precision disciplines through tremor suppression and decreased somatic anxiety. These sport-specific effects justify the selective prohibition adopted by the World Anti-Doping Agency. Further research is needed to clarify individual variability in response and to refine regulatory approaches.